Quantitative analysis of rural poverty in Nigeria - Omonona, Bolarin T. (International Food Policy Research Institute, 2010)
In spite of Nigeria's abundant natural and human resource endowment, poverty remains pervasive, multifaceted, and chronic. Given the most recent data available, it is estimated that approximately 69 million (or 54.4 percent) Nigerians lived in poverty in 2004, an increase of more than 24 percent since 1980. This brief deals with poverty in Nigeria and focuses on the determinants of poverty in rural households by identifying the household/community characteristics (such as the status of women) and region-specific risks that affect rural poverty and how they have changed over time.